FLR 2020
DOI: 10.14786/flr.v8i2.605
|View full text |Cite
|
Sign up to set email alerts
|

“I’m the best! Or am I?”: Academic self-concepts and self-regulation in kindergarten

Abstract: In this paper, we examined how kindergarteners' self-evaluation biases are related to behavioural self-regulation (SR) and learning goal orientation (GO). According to educational research and practice, fostering high and optimistic academic self-concepts promotes the setting of challenging goals and initiates effective behavioural SR processes. However, research on metacognition states that it is a match between academic self-concept and abilities that provides the optimal conditions for behavioural SR and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In a study that was conducted with first graders, Roebers et al (2012) reported that the students' domain-specific self-concepts were substantially associated with metacognitive monitoring. Finally, in a study that was conducted with kindergarteners, Compagnoni and Losenno (2020) found that their academic self-concepts positively related to their behavioral self-regulation.…”
Section: Mindsets Self-concepts Emotions and Their Relationship To Strategy Knowledgementioning
confidence: 98%
“…In a study that was conducted with first graders, Roebers et al (2012) reported that the students' domain-specific self-concepts were substantially associated with metacognitive monitoring. Finally, in a study that was conducted with kindergarteners, Compagnoni and Losenno (2020) found that their academic self-concepts positively related to their behavioral self-regulation.…”
Section: Mindsets Self-concepts Emotions and Their Relationship To Strategy Knowledgementioning
confidence: 98%
“…Educational research on diverse motivational beliefs has demonstrated that a growth mindset (Paunesku et al, 2015) or high self-concepts (Compagnoni and Losenno, 2020) are especially beneficial for academic underachievers. This finding has been explained by the notion that motivational beliefs play an important role especially in challenging situations when behavior must be actively self-regulated and when automatisms and routines can no longer be maintained.…”
Section: Academic Ability Level As Moderatormentioning
confidence: 99%